Enhancing the potential preclinical and clinical benefits of quercetin through novel drug delivery systems. Issue 1 (January 2020) - Khursheed, Rubiya; Singh, Sachin Kumar; Wadhwa, Sheetu; Gulati, Monica; Awasthi, Ankit
Highlights: Pharmacological activities and molecular targets of quercetin. Mechanistic pathways of quercetin for treating different diseases. Formulation strategies for improving the bioavailability of quercetin. Abstract : Quercetin is reported to have numerous pharmacological actions, including antidiabetic, anti-inflammatory and anticancer activities. The main mechanism responsible for its pharmacological activities is its ability to quench reactive oxygen species (ROS) and, hence, decrease the oxidative stress responsible for the development of various diseases. Despite its proven therapeutic potential, the clinical use of quercetin remains limited because of its low aqueous solubility, bioavailability, and substantial first-pass metabolism. To overcome this, several novel formulations have been reported. In this review, we focus on the applications of quercetin extract as well as its novel formulations for treating different disorders. We also examine its proposed mechanism of action of quercetin.